Biological control by Plant Growth Promoting Rhizobacteria - Bestami, Merdia (Algerian Journal of Biosciences, 2020)
Plant Growth Promoter Rhizobacteria (PGPR) is soil bacteria that can live on, in or around plant tissue and promote plant growth by many mechanisms that include a biological control of plant pathogens. Indeed, PGPRs have a protective effect through several modes of action such as antagonism, competition, production of hydrolytic enzymes and biofilm formation. Moreover, the use of PGPRs as biocontrol agents is very harmonious with the environment and therefore represents a good alternative to the use of chemicals in agriculture. This review is presented as a general bibliographical synthesis on the different aspects of PGPRs and their biocontrol potential.